Self Help Groups as a Support System: Their Influence on Stress Levels in New Nursing Students - Nabilah, Charizatun; Fitrianur, Widya Lita; Widiyawati, Wiwik; Zuhroh, Diah Fauzia (INNOVATION RESEARCH JOURNAL, 2024)
New students must adapt to a new environment because of the differences in the nature of education in Senior High School (SMA) and college. If students are unable to meet the demands in college, it can cause stress. One of the therapeutic activities that aims to improve and maintain mental health in students is Self Help Group (SHG) therapy . The purpose of this study was to determine the effect of Self Help Group (SHG) on stress levels in new students of the Nursing Study Program at the University of Muhammadiyah Gresik. This study uses a one group pretest-posttest approach. The population is 48 new students of the Nursing Study Program, Muhammadiyah University of Gresik, class of 2023. The sampling technique uses total sampling , with the research sample being all new students of the Nursing Study Program. Data collection uses questionnaires and Self Help Group (SHG) therapy observation sheets. Data analysis uses the parametric statistical test of the paired T-test (Paired Sample T-Test). The results of the study on stress levels before being given Self Help Group (SHG) therapy were that almost half of the students experienced severe stress as many as 21 (48.8%) and after being given Self Help Group (SHG) therapy, almost half of them experienced a decrease in severe stress levels in new students as many as 16 (37.2%) students. The results of the Paired Sample T-Test statistical test obtained a ρ value of 0.038 <α 0.05. There is an influence of Self Help Group (SHG) on stress levels in new students of the Nursing Science Study Program, Muhammadiyah University of Gresik.